KESIAPAN ANAK SAAT MEMASUKI SEKOLAH DASAR - Zusy Aryanti (Jurusan PGMI FTIK IAIN Metro Lampung, 2015)
School readiness is a physical and psychological maturity at the time the child will enter elementary school. Not only academic readiness, but also the readiness of physical, emotional and social development of children contribute to the next development phase. School readiness in children can be seen through the test NST (Nijmeegse Schoolbekwaamheids Test), which is a test used to determine the extent to which children have school readiness.